Preliminary phytochemical, microscopic analysis and metabolite profiling of Phoenix pusilla root - Anuradha Pradeep, S. Vijaya Bharathi, M. Syed Ali (Journal of Applied Pharmaceutical Science, 2019)
Palms are considered as familiar strangers. Various studies reported that the genus Phoenix was mostly cultivated, traditionally used plants as medicine, and also as an ornamental plant. In this present study, preliminary phytochemical analysis, the study of microscopical structures and the chemical constituents of Phoenix pusilla root was evaluated. Transverse Section of P. pusilla root was studied by sectioning the two different thickness roots and also powder microscopy was carried out. Non-polar, volatile constituents of crude ethanolic extract of root were analyzed by GC–MS. Primary and secondary metabolites quantification revealed that the carbohydrate content and total phenolics concentration were higher than the other metabolites. The physicochemical analysis showed the moisture content was 3.78 ± 0.54, the ash content value was 2.46 ± 0.95, and the crude fiber content was higher than protein, fat content. Microscopy study showed the presence of unique tracheids. Metabolite profiling revealed the presence of 96 different constituents and more than 10 found to have biological importance. Pharmacognostic study is an important step of research which reveals about shelf-life of the drug, adulterations, etc.
Keywords: GC-MS, Phoenix pusilla root, phytochemical analysis, microscopic study, shelf-life.